Age-dependent expression of the erythropoietin gene in rat liver and kidneys. - Eckardt, K; Ratcliffe, P; Tan, C; Bauer, C; Kurtz, A (1992)
Using RNAse protection, we have made quantitative measurements of erythropoietin (EPO) mRNA in liver and kidneys of developing rats (days 1-54), to determine the relative contribution of both organs to the total EPO mRNA, to monitor changes which occur with development, and to compare the hypoxia-induced accumulation of EPO mRNA with the changes in serum EPO concentrations. To determine whether developmental and organ-specific responsiveness is related to the type of hypoxic stimulus, normobaric hypoxia was compared with exposure to carbon monoxide (functional anemia). Under both stimuli EPO mRNA concentration in liver was maximal on day 7 and declined during development. In contrast, EPO mRNA concentration in kidney increased during development from day 1 when it was 30-65% the hepatic concentration to day 54 when it was 12-fold higher than in liver. When organ weight was considered the liver was found to contain the majority of EPO mRNA in the first three to four weeks of life, and although, in stimulated animals, the hepatic proportion declined from 85-91% on day 1, it remained approximately 33% at day 54 and was similar for the two types of stimuli. When normalized for body weight the sum of renal and hepatic EPO mRNA in animals of a particular age was related linearly to serum hormone concentrations. However, the slope of this regression increased progressively with development, suggesting age-dependent alterations in translational efficiency or EPO metabolism.